Disegno dell'architettura : Appunti per la didattica - Paola Puma (Firenze University Press, 2003)
The book emerged as a collection of the lessons held for students on the Architectural Design courses, and is conceived as a tool for orientation within the various fields of the discipline: from the preparatory phase of graphic training, to the application of the principles of geometrical representation, through to the conventional technical representation of architecture. Considerable space is devoted, not only to imaginative drawing, but also to relief drawing, applied first to figurative architecture and subsequently to the real city. In view of the nature of the book, designed as an aid to learning, the text is presented in the form of working notes which have the primary intention of illustrating the pictures.
Keywords: Disegno architettonico; Architettura; Disegno; Grafica